Effectiveness of selected Yoga postures and procedures for improvement in pulmonary functions in 8-14 year old children of Nasobronchial allergy - Mridu Gupta; Swaran Jit; Paramjit Kaur (International Journal of Medical Research and Review, 2017)
Introduction: Yoga postures can be effective way to regularize immune functions. Nasobronchial allergy appears when immune mechanisms go haywire and start behaving autonomously. Yoga has been used in many centers in India to cure asthma and other allergic ailments. This systematic prospective control trial study was done on school going children of Amritsar District.,India.Material & Methods: Study done on 150 school going 8-14 year old children taken from Paediatrics ward of GND hospital, Amritsar. 75 children were included in study group and another 75 children were taken as controls. Both study and control group was further divided into three groups each. Sub-group-A- Allergic Rhinitis, Sub-group-B- Bronchial Asthma, Sub-group-C- Allergic Rhinitis and Bronchial Asthma both. Study group were taught certain Yoga postures like Virassna, Stupassna etc. and were followed for 6-12 weeks and results were recorded at 0, 6 and 12 weeks. Pulmonary functions tests were done on computerized spirometer.Results: In sub-group A and B highly significant (p<0.001) results were seen in study group in terms of improvements in FVC, FEV1and PEFR as compared to control group.Conclusion: Yoga postures and its variant breathing exercises can effectively improve pulmonary functions and modulate immune functions for cure of allergy.